Analysis of resistance‐associated substitutions in acute hepatitis C virus infection by deep sequencing across six genotypes and three continents. Issue 1 (25th September 2016) - Eltahla, A. A.; Rodrigo, C.; Betz‐Stablein, B.; Grebely, J.; Applegate, T.; Luciani, F.; Schinkel, J.; Dore, G. J.; Page, K.; Bruneau, J.; Morris, M. D.; Cox, A. L.; et al.
Summary: Several direct‐acting antivirals (DAAs) have been approved for the treatment of chronic hepatitis C virus (HCV) infections, opening the door to highly effective interferon‐free treatment regimens. Resistance‐associated substitutions (RASs) have been reported both in treatment‐naïve patients and following treatment with protease (NS3), phosphoprotein (NS5A) and polymerase (NS5B) inhibitors. The prevalence of naturally occurring RASs in untreated HCV‐infected individuals has mostly been analysed in those infected with genotype 1 (GT1), in the late phase of infection, and only within limited regions of the genome. Furthermore, the geographic distribution of RASs remains poorly characterized. In this study, we used next‐generation sequencing to analyse full‐length HCV genomes for the prevalence of RASs in acute HCV infections identified in nine international prospective cohorts. RASs were analysed in 179 participants infected with all six major HCV genotypes (GT1‐GT6), and the geographic distribution of RASs was assessed in 107 GT1a and GT3a samples. While RASs were detected at varied frequencies across the three genomic regions, and between genotypes, RASs relevant to multiple DAAs in the leading IFN‐free regimens were rarely detected in combination. Low‐frequency RASs (<10% of the viral population) were also shown to have a GT‐specific distribution. The main RASs with geographic associations were NS3 Q80K in GT1a samples and NS5B N142T in GT3a. These data provide the backdrop for prospective surveillance of RASs during DAA treatment scale‐up.